Estimation of the Benchmark Dose for Right-Censored Lifetime Data - Chen, Yuh-Ing; Lin, Wen-Ming (Communications in statistics. Simulation and computation, 2015)
In this paper, we consider estimating the benchmark dose in a dose-response study with right-censored lifetime data, where the benchmark dose is the dose corresponding to a specific benchmark response, which is related to the probability that the lifetime of a subject receiving the dose is too short. Under the Cox or Weibull extension proportional hazards model, simultaneous lower confidence limits on the benchmark dose are developed. We further conduct a Monte Carlo study to investigate the performance of the proposed lower confidence limits. Finally, a real dataset is illustrated to demonstrate the application of the proposed procedures.